Electroacupuncture reduces astrocyte number and oxidative stress in aged rats with surgery-induced cognitive dysfunction. Issue 8 (August 2019) - Liu, Pei-Rong; Cao, Feng; Zhang, Yu; Peng, Sheng
Objectives: To investigate the effects of electroacupuncture in regulating astrocytes and oxidative stress in a rat model of postoperative cognitive dysfunction (POCD). Methods: Male aged Sprague-Dawley rats were randomized to undergo left hepatic lobe resection to induce POCD, followed by either electroacupuncture or no treatment; or similar surgery without left lobe resection or electroacupuncture (sham). Postsurgical cognitive function, hippocampal astrocyte number and oxidative stress indicators were measured. Results: At days 1, 3 and 7 following surgery, escape latency was significantly shorter and platform crossing frequency was increased with electroacupuncture versus other groups. At postoperative day 1, the electroacupuncture group showed significantly fewer glial fibrillary acidic protein (GFAP)-positive hippocampal astrocytes versus the POCD model group. In POCD rats, electroacupuncture significantly decreased serum S100 calcium binding protein B and neuron-specific enolase levels, and increased brain-derived neurotrophic factor and glial cell-derived neurotrophic factor levels, at days 1, 3 and 7. Electroacupuncture significantly attenuated the hippocampal POCD-induced increase in malondialdehyde and decreased superoxide dismutase levels at day 1 following surgery. Conclusion: Electroacupuncture may improve cognitive function in rats with POCD by reducing hippocampal GFAP-positive astrocyte number and suppressing oxidative stress.